From Beijing to Port Moresby. - Domingues, Virginia and Wu (Taylor and Francis, 2014)
Essays in this volume focus on Singapore, Papua New Guinea, Taiwan, Japan, Thailand, and the People's Republic of China as sites rife with discursive complexity. From small to large, young to old, former colony to former colonial power, these six examples do well to represent situated voices and cultural values meted out in a larger ""global"" space.